Eriocaulaceae from Serra do Caraça, Minas Gerais, Brazil - Soldevila, Ambar; Echternacht, Livia (Rodriguésia, 2024)
Abstract The Serra do Caraça, located in Minas Gerais state, Brazil, hosts a remarkable biological diversity, comprising rare and endemic plant species. Several naturalists have visited the area since the XIX century and made important botanical collections, many of these established as type specimens to describe different taxa, including Eriocaulaceae (Poales) species and varieties. This work provides a floristic treatment of Eriocaulaceae from Serra do Caraça, presenting species descriptions, distribution map, photographs, identification key, and notes on phenology and distribution. Thirty-three species were recorded in five genera, and Paepalanthus is the most numerous with 21 species, followed by Leiothrix (6 spp.), Syngonanthus (3 spp.), Comanthera (2 spp.), and Eriocaulon (1 sp.). Notable, among those are four species endemic to the Quadrilátero Ferrífero, one micro-endemic to the Serra do Caraça, and 16 endemic to Minas Gerais state. Five new synonyms are proposed. Eighteen taxa have type materials described to Serra do Caraça, corresponding to 12 species, five varieties, and one forma. Resumo A Serra do Caraça, localizada no estado de Minas Gerais, Brasil, possui uma notável diversidade biológica, com espécies raras e endêmicas. Vários naturalistas visitaram a área desde o século XIX e fizeram importantes coleções botânicas, várias destas designadas como espécimes tipo para descrever táxons, incluindo espécies e variedades de Eriocaulaceae. Este trabalho provê um tratamento florístico de Eriocaulaceae para a Serra do Caraça, apresentando a descrição das espécies, mapa de distribuição, fotos, chave de identificação, e informações sobre fenologia e distribuição. Trinta e três espécies foram registradas em cinco gêneros, sendo Paepalanthus o mais numeroso com 21 espécies, seguido por Leiothrix (5 spp.), Syngonanthus (3 spp.), Comanthera (2 spp.) e Eriocaulon (1 sp.). Destacam-se quatro espécies endêmicas para o Quadrilátero Ferrífero, uma micro-endêmica para a Serra do Caraça, e 16 espécies endêmicas para Minas Gerais. Propomos cinco novos sinônimos. Dezoito táxons possuem material tipo descrito para a Serra do Caraça, sendo 12 espécies, cinco variedades, e uma forma.